PET (Polyethylene Terephthalate) composition as well as preparation method and application thereof

By using a combination of homopolymer PET resin, ethylene copolymer ionomer and ether ester plasticizer in PET materials, the problem of poor solder resistance in the soldering process of existing PET materials is solved, and the comprehensive improvement of high crystallinity, high temperature resistance, toughness and fluidity of the material is achieved.

CN119684756AActive Publication Date: 2025-03-25KINGFA SCI & TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411599287.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-25
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing flame retardant enhanced modified PET materials have poor solder resistance during the soldering process, and the soldering parts are prone to blackening, resulting in a high defect rate and difficult to take into account the high toughness and high fluidity of the materials.

Method used

Homopolymer PET resin is used as the matrix resin, and ethylene copolymer ionomer and ether ester plasticizer are added to improve the crystallization degree and molecular chain activity of the material through heterophasic nucleation and hydrogen bonding, thereby improving the comprehensive performance of soldering resistance, toughness and fluidity.

Benefits of technology

It significantly improves the crystallization degree and high temperature resistance of PET materials, enhances the resistance to soldering blackening, reduces the defective rate of soldering products, and maintains high toughness and high fluidity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a PET composition as well as a preparation method and application thereof, and belongs to the technical field of engineering plastics. According to the PET composition, the homopolymerized PET resin is selected as matrix resin, the first tin-resistant flux ethylene copolymer ionomer and the second tin-resistant flux-specific ether ester plasticizer are added, the content of all the components is controlled within a specific range, and meanwhile the PET composition has good tin soldering resistance, high toughness and high flowability, is suitable for preparing electronic and electrical products and has good application prospects. Such as a coil framework.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of engineering plastics, and in particular to a PET composition and a preparation method and application thereof. Background Art

[0002] Polyethylene terephthalate (PET) is a semi-crystalline thermoplastic polyester. The main modifications of PET are reinforcement modification and flame retardant reinforcement modification. Among them, flame retardant reinforcement modified PET products are often used in the electronic and electrical industry (such as coil skeletons, housings, etc.). The material is required to meet the requirements of solder resistance so that it can be used to connect with metal parts; the material is also required to have high toughness to meet the functional test of the product; at the same time, the material is required to have high fluidity to meet the requirements of injection molding. Therefore, it is necessary to develop a PET material that has the properties of solder resistance, high toughness and high fluidity. Summary of the invention

[0003] Based on the defects of the prior art, the purpose of this application is to provide a PET composition and a preparation method and application thereof, aiming to make the PET material have the properties of solder resistance, high toughness and high flowability at the same time.

[0004] In order to achieve the above objectives, in a first aspect, the present application provides a PET composition comprising the following components in parts by weight:

[0005]

[0006] The first tin-resistant solder is an ethylene copolymer ionomer;

[0007] The second solder-resistant agent is an ether-ester type plasticizer, comprising at least one of the compounds of formula I,

[0008]

[0009] wherein R1 and R2 are each independently a C7-C9 alkyl group, and n is an integer of 7 or less;

[0010] The PET resin is a homopolymer PET resin.

[0011] Conventional flame-retardant reinforced modified PET materials have poor soldering resistance, and the soldering parts are prone to blackening, resulting in a high defective rate. This application uses homopolymer PET resin as the base resin, because the isophthalic acid (IPA) content of homopolymer PET resin is 0, and compared with copolymer PET resin, it has better crystallinity and can improve the crystallization performance of the material system; at the same time, a first solder-resistant ethylene copolymer ionomer is added as a nucleation site for heterogeneous nucleation, and the ethylene copolymer ionomer contains EAA units (i.e., ethylene-acrylic acid units) and metal ions, wherein the metal ions are nucleation centers, and the carboxyl groups of the EAA units react with the terminal hydroxyl groups in the PET resin, prompting the PET resin to nucleate toward the metal ions. Center migration can greatly improve the crystallization performance of the material system; in addition, a second tin-resistant solder ether ester plasticizer is added. The ether ester plasticizer has a specific structure, an n value of less than 7, a low molecular weight, good compatibility with PET resin, and is easy to disperse in the PET resin. Moreover, there is a hydrogen bond between the ether bonds and ester groups contained therein and the ester groups and hydroxyl groups in the PET resin, which can greatly improve the activity of the PET molecular chain, so that the PET molecular chain can arrange the lattice more quickly when arranging toward the nucleation site, thereby improving the crystallization degree of the system. Under the synergistic effect of a specific content of homopolymer PET resin, the first tin-resistant solder ethylene copolymer ionomer and the second tin-resistant solder ether ester plasticizer, the PET composition of the present application has a high degree of crystallization, good high temperature resistance, strong ability to resist soldering blackening, and a low defective rate of soldering products.

[0012] The content of the first solder-resistant ethylene copolymer ionomer and the toughening agent will affect the fluidity of the material. By controlling the content of the two within the above-mentioned specific range, they can effectively play the role of increasing crystallinity or improving toughness while ensuring that the material has high fluidity.

[0013] The PET composition of the present application has good solder resistance, high toughness and high fluidity under the combined effect of the above-mentioned components in specific amounts.

[0014] Preferably, n is an integer of 2 to 7. For example, n is 2, 3, 4, 5, 6 or 7.

[0015] Preferably, the melt flow rate (melt flow rate is melt index) of the first tin-resistant solder at a temperature of 190°C and a load of 2.16 kg is 0.7-15 g / 10 min. More preferably, the melt flow rate of the first tin-resistant solder at a temperature of 190°C and a load of 2.16 kg is 4-6 g / 10 min.

[0016] When the melt flow rate of the first tin-resistant solder under the conditions of temperature 190°C and load 2.16kg is in the range of 0.7-15g / 10min, especially in the range of 4-6g / 10min, the material has a stronger ability to resist soldering blackening and a lower defective rate of soldered products. The melt flow rate of the first tin-resistant solder under the conditions of temperature 190°C and load 2.16kg can be selected as 0.7g / 10min, 0.8g / 10min, 0.9g / 10min, 1g / 10min, 2g / 10min, 3g / 10min, 4g / 10min, 5g / 10min, 6g / 10min, 7g / 10min, 8g / 10min, 9g / 10min, 10g / 10min, 11g / 10min, 12g / 10min, 13g / 10min, 14g / 10min, 15g / 10min or a range formed by any two of the above values.

[0017] The melt flow rate of the first tin-resistant solder is measured with reference to ISO 1133-1:2011.

[0018] Preferably, the cation in the first tin-resistant solder is at least one of sodium ion, calcium ion and zinc ion. More preferably, the cation in the first tin-resistant solder is zinc ion. When the cation in the first tin-resistant solder is zinc ion, the material has a stronger ability to resist blackening during soldering, and the defective rate of soldered products is lower.

[0019] Preferably, the intrinsic viscosity of the PET is 0.6-0.9 dL / g.

[0020] The intrinsic viscosity of PET is closely related to processing performance, mechanical properties (such as Izod notched impact strength), etc. When the intrinsic viscosity of PET is controlled within the above range, the comprehensive performance of processing performance and mechanical properties (such as Izod notched impact strength) of the material is better.

[0021] The intrinsic viscosity test method of PET: the intrinsic viscosity of PET is determined by referring to the capillary viscometer method in 5.1.1 Method A of GB / T 14190-2017, and the selected solvent is phenol and 1,1,2,2-tetrachloroethane (mass ratio is 50:50).

[0022] Preferably, the toughening agent includes at least one of ethylene-butyl acrylate-glycidyl methacrylate terpolymer and ethylene-methyl acrylate-glycidyl methacrylate terpolymer.

[0023] The type of toughening agent will affect the fluidity of the material. When at least one of ethylene-butyl acrylate-glycidyl methacrylate terpolymer and ethylene-methyl acrylate-glycidyl methacrylate terpolymer is used as a toughening agent, the toughness of the material can be improved to a greater extent with a smaller addition amount, while ensuring that the material has better fluidity.

[0024] Preferably, the content of glycidyl methacrylate (GMA) in the ethylene-butyl acrylate-glycidyl methacrylate terpolymer is 3-8 wt.%.

[0025] Preferably, the content of glycidyl methacrylate (GMA) in the ethylene-methyl acrylate-glycidyl methacrylate terpolymer is 3-8 wt.%.

[0026] Preferably, the glass fiber is an alkali-free glass fiber with a diameter of 10-13 μm and a length of 3.0-4.5 mm.

[0027] Preferably, the following components in parts by weight are also included:

[0028] Antioxidant 0.2-0.5 parts,

[0029] Lubricant 0.5-1.2 parts.

[0030] Preferably, the flame retardant comprises at least one of brominated polystyrene and brominated epoxy resin.

[0031] Preferably, the antioxidant includes at least one of hindered phenol (pentaerythritol ester), phosphite, and thioether.

[0032] Preferably, the lubricant includes at least one of pentaerythritol ester and oxidized polyethylene wax.

[0033] Preferably, the mass fraction of the PET resin in the PET composition is above 44%, such as 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58% or a range formed by any two of the above.

[0034] In a second aspect, the present application provides a method for preparing the PET composition, comprising the following steps: mixing the raw materials except the glass fiber and adding the mixed materials into a twin-screw extruder from a main feed port, and adding the glass fiber into the twin-screw extruder from a side feed port, melt-extruding, cooling and granulating to obtain the PET composition.

[0035] Preferably, the melt extrusion satisfies: temperature of 220-270°C, screw speed of 250-400 rpm, feed rate of 50-200kg / h, and vacuum degree of -0.1-0MPa. More preferably, the barrel temperature of the twin-screw extruder from the main feed port to the die is: 220-240°C, 230-250°C, 230-250°C, 230-250°C, 240-260°C, 240-260°C, 240-260°C, 250-270°C, 250-270°C and 250-270°C.

[0036] In a third aspect, the present application provides the use of the PET composition in preparing a coil skeleton.

[0037] Compared with the prior art, the beneficial effects of this application are:

[0038] (1) The PET composition of the present application has a higher degree of crystallinity, higher high temperature resistance, stronger resistance to soldering blackening, and a lower defective rate of soldered products by selecting homopolymer PET resin as the base resin and adding a first solder-resistant ethylene copolymer ionomer and a second solder-resistant ether ester plasticizer.

[0039] (2) The PET composition of the present application has good solder resistance, high toughness and high fluidity under the combined effect of the various components in specific amounts, and is suitable for preparing electronic and electrical products, such as coil skeletons, etc. DETAILED DESCRIPTION

[0040] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.

[0041] The raw materials used in the following examples and comparative examples are shown in Table 1, and unless otherwise specified, they are all commercially available raw materials. In addition, the component raw materials used in each parallel experiment are all of the same kind.

[0042] Table 1

[0043]

[0044]

[0045] In Table 1, the melt index of 0.9 g / 10 min@190°C / 2.16 kg means that the melt index is 0.9 g / 10 min under the test conditions of temperature 190°C and load 2.16 kg. The same applies to other similar expressions.

[0046] Each of the following examples and comparative examples provides a PET composition, comprising the following steps: mixing raw materials other than glass fiber and adding them to a twin-screw extruder from a main feed port, adding glass fiber to the twin-screw extruder from a side feed port, melt-extruding, cooling and granulating to obtain a PET composition, wherein the melt extrusion satisfies:

[0047] The barrel temperatures of the twin-screw extruder from the main feed port to the die are: 220-240℃, 230-250℃, 230-250℃, 230-250℃, 240-260℃, 240-260℃, 240-260℃, 250-270℃, 250-270℃ and 250-270℃, the screw speed is 250-400 rpm, the feed rate is 50-200kg / h, and the vacuum degree is -0.1~0MPa.

[0048] The formulations of the PET compositions of these examples and comparative examples are shown in Tables 2 and 3.

[0049] Table 2

[0050]

[0051]

[0052] Table 3

[0053] Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Embodiment 15 Example 16 Embodiment 17 Embodiment 18 PET resin 1 52 50 52 50 46 56 51 51 First tin-resistant solder 3 1 3 2 2 2 2 2 2 Second tin-resistant solder 1 2 2 1 3 2 2 2 2 Toughener 1 1 1 1 1 1 1 0.5 2 Flame retardants 13 13 13 13 13 13 15 10 Fiberglass 30 30 30 30 35 25 28.5 31.6 Antioxidants 0.3 0.3 0.3 0.3 0.3 0.3 0 0.2 Lubricants 0.7 0.7 0.7 0.7 0.7 0.7 0 1.2

[0054] The following performance tests were performed on the above embodiments and comparative examples, and the test results are shown in Table 4.

[0055] Soldering defective rate: After the material is baked at 120℃ for 4 hours, 100 skeleton products are injection molded and soldering tests are performed on these skeleton products. If the soldering parts are not blackened, they are qualified; otherwise, they are unqualified and defective, and the defective rate is calculated.

[0056] DSC (Differential Scanning Calorimetry) Crystallization Temperature: After the material is baked at 120°C for 4 hours, it is injection molded into a standard curved specimen. 8 mg of material is cut from the curved specimen and placed in a crucible to make a standard test sample. The test is performed according to the test standard ISO11357-1:2016. The test conditions are: 30-300°C, heating rate 10°C / min, 1.5C, N2 atmosphere.

[0057] Izod notched impact strength: test standard ISO 180-2019, pendulum energy 2.75J, type A notch.

[0058] Spiral length: Set the injection temperature to 270 degrees Celsius, use a spiral mold, and inject the spiral under the same injection molding process conditions to test the spiral length.

[0059] Table 4

[0060]

[0061]

[0062] From the above data, it can be seen that the materials of each embodiment have good solder resistance, high toughness and high fluidity, such as DSC crystallization temperature above 220°C, solder defective rate below 3%, and cantilever beam notched impact strength above 9kJ / m 2 Above, the spiral line length is more than 210mm.

[0063] Comparative Example 1 did not add ethylene copolymer ionomer, the material crystallinity was low, and the soldering defective rate was high.

[0064] In Comparative Example 2, no ether ester plasticizer was added, the material crystallinity was low, and the soldering defective rate was high.

[0065] Comparative Example 3 did not add a toughening agent, and the material's Izod notched impact strength was relatively low.

[0066] In Comparative Example 4, the amount of ethylene copolymer ionomer added is excessive. It itself contains ethylene copolymer, which has a similar structure to the toughening agent. The excessive ethylene copolymer structure will lead to a decrease in the melt index of the system. At the same time, it is ionized and has no effect on the toughening of the system. On the contrary, the presence of excessive ions will reduce the cantilever beam notched impact strength of the system.

[0067] In comparative example 5, the amount of ether ester plasticizer added is excessive. The ether ester plasticizer mainly improves the activity of the molecular chain of PET. When the content of ether ester plasticizer is too high, the excess part will not play a role in improving the activity of the molecular chain of PET, but will reduce the viscosity of the system (increase fluidity), thereby resulting in low cantilever beam notched impact strength of the material.

[0068] In Comparative Example 6, the amount of toughening agent added is excessive, which is not conducive to the flow of the material and causes the length of the spiral line to be relatively low.

[0069] The PET resin used in Comparative Example 7 is a copolymerized PET resin, which has poor crystallinity, resulting in a low crystallization temperature of the material and a high soldering defective rate.

[0070] The n value of the ether ester plasticizer used in Comparative Example 8 is too large, resulting in its viscosity being too high, making it difficult to disperse in the system and difficult to effectively disperse in the PET resin, which affects its ability to improve the activity of the PET molecular chain, resulting in a low crystallization temperature of the material and a high solder defective rate.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A PET composition, characterized in that It comprises the following components in parts by weight: The first tin-resistant solder is an ethylene copolymer ionomer; The second solder-resistant agent is an ether-ester type plasticizer, comprising at least one of the compounds of formula I, wherein R1 and R2 are each independently a C7-C9 alkyl group, and n is an integer of 7 or less; The PET resin is a homopolymer PET resin.

2. The PET composition according to claim 1, characterized in that The n is an integer of 2-7.

3. The PET composition according to claim 1, characterized in that The melt flow rate of the first tin-resistant solder at a temperature of 190° C. and a load of 2.16 kg is 0.7-15 g / 10 min, preferably 4-6 g / 10 min.

4. The PET composition according to claim 1, characterized in that The cation in the first tin-resistant solder is at least one of sodium ion, calcium ion and zinc ion, preferably zinc ion.

5. The PET composition according to claim 1, characterized in that The intrinsic viscosity of the PET is 0.6-0.9 dL / g.

6. The PET composition according to claim 1, characterized in that The toughening agent includes at least one of ethylene-butyl acrylate-glycidyl methacrylate terpolymer and ethylene-methyl acrylate-glycidyl methacrylate terpolymer.

7. The PET composition according to claim 1, characterized in that At least one of the following conditions is met: S1. The glass fiber is an alkali-free glass fiber having a diameter of 10-13 μm and a length of 3.0-4.5 mm; S2 The flame retardant comprises at least one of brominated polystyrene and brominated epoxy resin; S3. also contains the following components by weight: Antioxidant 0.2-0.5 parts, Lubricant 0.5-1.2 parts, The antioxidant includes at least one of hindered phenol (pentaerythritol ester), phosphite, and thioether. The lubricant includes at least one of pentaerythritol ester and oxidized polyethylene wax.

8. The method for preparing the PET composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing raw materials except glass fiber and adding the raw materials into a twin-screw extruder from a main feed port, adding glass fiber into the twin-screw extruder from a side feed port, melting and extruding, cooling and granulating to obtain the PET composition.

9. The method for preparing the PET composition according to claim 8, characterized in that: The melt extrusion meets the following conditions: temperature of 220-270° C., screw speed of 250-400 rpm, feed rate of 50-200 kg / h, and vacuum degree of -0.1 to 0 MPa.

10. Use of the PET composition according to any one of claims 1 to 7 in preparing a coil skeleton or a shell.

Citation Information

Patent Citations

  • High-toughness polyester resin alloy composition and preparation method thereof

    CN106633681A

  • High-fluidity black flame-retardant reinforced polyethylene glycol terephthalate composition and preparation method thereof

    CN112521729A

  • High-friction-welding-strength flame-retardant reinforced PET (Polyethylene Terephthalate) composition as well as preparation method and application thereof

    CN115678218A

  • Method for soldering electronic parts

    JP1997162537A